When Ejaculation Becomes the Goal in Itself: A Psychodynamic Approach to Delayed Ejaculation. Issue 3 (May 2021) - Sandström, Eddie; Fugl-Meyer, Kerstin S.
There are a group of men with delayed ejaculation (DE) where the etiology as well as the consequences of the dysfunction are unclear. The aim of the present study was to explore, from a psychodynamic perspective, personality traits among men seeking treatment due to DE. During a 2.5-year period, a consecutive series of 14 men with DE were seeking help at Karolinska University hospital, Sweden. Full medical history and physical examination, sexological case-history and psychological assessments were performed by physicians and a psychotherapist. The results found all patients to be healthy. Mean age was 34 years (range 20–43 years). No other sexual dysfunction occurred. With one exception, they were sexually active. The psychological assessment (The Karolinska Psychodynamic Profile; KAPP) found patients to have difficulties in areas of dependency and separation, control and impulse control, regression in the service of the ego, coping with aggressive affects, alexithymic traits, sexual function, and satisfaction. The results add a deeper understanding of personality traits among healthy patients with DE, which may be a tool for the case history, and offer new treatment strategies. We suggest that DE can be the physical manifestation of some specific personality difficulties, and thus, ejaculation becomes the goal in itself and not the climax of an enjoyable adventure.